Peningkatan Awareness, Pengetahuan, dan Sikap dalam Keselamatan Berkendara (Safety Riding) bagi Penghuni Asrama Mahasiswa Sekitar Distrik Heram - Monita Yessy Beatrick; Elisabeth Veronika Wambrauw (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
The high number of accidents due to alcoholic drinks in 2020 caused 201 people to die, 184 people were seriously injured, and 417 other people suffered minor injuries, making the provinces of Papua and North Sulawesi the provinces with the highest number of accidents due to the influence of alcoholic drinks. The aim of developing this community is to provide education to motorists in Jayapura City, for the area around Waena, Jayapura City. Increasing drivers' awareness of the dangers of driving under the influence of alcoholic beverages and improving traffic safety attitudes in the youth community in boarding houses around Heram Abepura sub-district. By using video lecture and game methods. This service activity was carried out in three student dormitories, namely the Yahukimo Dormitory, the Papua Regional Government Mess and the BEOPRITS Asmat Dormitory. The results of this service are intended for the participants